Articulatory Errors in Qur'anic Recitation: A Qualitative Investigation of Makhārij al-Ḥurūf Mastery among Indonesian Tahfizh Students - Rahmia Mailani Putri; Fakhriyah Annisa Afroo (AL-ADABIYAH: Jurnal Pendidikan Agama Islam, 2026)
The accurate articulation of Arabic letters is a fundamental requirement for proper Qur’anic recitation. However, pronunciation errors in makhārij al-ḥurūf remain prevalent among students participating in Qur’anic memorization programs. This study aims to investigate the forms of articulatory errors in Qur’anic recitation and identify the factors influencing makhārij al-ḥurūf mastery among tahfīẓ extracurricular students at SMA Negeri 2 Batang Anai, Indonesia. A qualitative descriptive approach was employed. Data were collected through recitation observations, semi-structured interviews, and document analysis involving students and tahfīẓ instructors selected through purposive sampling. Data were analyzed using the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing, while credibility was ensured through source and technique triangulation. The findings revealed pronunciation errors in fourteen hijaiyah letters, with the highest error rates occurring in ḍād (ض) (100%), followed by ẓāʾ (ظ) and ghayn (غ) (80%), and ʿayn (ع) (60%). These errors were associated with inaccurate articulation points, limited mastery of ṣifāt al-ḥurūf, insufficient theoretical understanding of makhārij al-ḥurūf, inadequate recitation practice, inconsistent participation in tahfīẓ activities, suboptimal program implementation, and first-language interference. The originality of this study lies in its integration of articulatory phonetics and Qur’anic pedagogy to explain pronunciation difficulties among Indonesian tahfīẓ students. This study contributes to the literature by demonstrating that recitation errors are shaped by both linguistic and educational factors, highlighting the importance of combining tajwīd instruction with systematic articulatory training to improve Qur’anic recitation proficiency.